Tangeretin derivative, 5-acetyloxy-6, 7, 8, 4′-tetramethoxyflavone induces G2/M arrest, apoptosis and autophagy in human non-small cell lung cancer cells in vitro and in vivo. Issue 1 (2nd January 2016) - Li, Yi Rong; Li, Shiming; Ho, Chi-Tang; Chang, Ya-Han; Tan, Kok-Tong; Chung, Ting-Wen; Wang, Bing-Yen; Chen, Yu-Kuo; Lin, Chi-Chen
ABSTRACT: Tangeretin, a major phytochemicals in tangerine peels - an important Chinese herb, has been found to have anti-carcinogenic properties. To improve bioavailability and increase potency of tangeretin, its derivative, 5-acetyloxy-6, 7, 8, 4′-tetramethoxyflavone (5-AcTMF), has been synthesized and shown potent inhibition of proliferation activity against human breast and leukemia cancer cell lines. In this study, we have further investigated the anticancer effects of 5-AcTMF on CL1-5 non-small cell lung cancer cells (NSCLC) both in vitro and in vivo and demonstrated that 5-AcTMF effectively inhibited cancer cell proliferation, induced G2/M-phase arrest associated with cdc2 and CDC25c and increased in the apoptotic cells associated with caspase activation, down regulation of Bcl-2, XIAP and Survivn, inducing release of cytochrome c into the cytosol and disruption of mitochondrial membrane potential. We also found that 5-AcTMF treatment of CL1-5 activated autophagy, indicated by triggered autophagosome formation and increased LC3-II levels and formation of LC3 puncta. Moreover, we also found that 5-AcTMF lowered phophoatidylinositol 3-kinase/AKT/mTOR signaling pathway. Over-expression of AKT by AKT cDNA transfection decreased 5-AcTMF mediated apoptosis and autophagy, supporting the induction of apoptosis and autophagy by inhibition of AKT pathway. In an animal study, 5-AcTMF effectively delayed tumor growth in a nude mouse model of CL1-5 xenografts without observed adverse effect. Immunohistochemistry Analysis indicated that 5-AcTMF induced CL1-5 cell apoptosis and autophagy in vivo. Taken together, these data demonstrate that 5-AcTMF is a novel small molecule agent that can inhibit NSCLC cell proliferation, and induce G(2)/M phase arrest and via the mitochondrial apoptotic pathway and autophagy.